Women in sport leadership positions in Malaysia: issues and challenges - Aman, Mirian Pabatao; Hanapi, Suharyanti; Yusof, Aminuddin; Mohamed Razali, Abu Bakar; Omar Dev, Roxana Dev (Human Resource Management Academic Research Society, 2019)
Leadership is the process of influencing an organized group toward accomplishing common set goals, and it can also be defined as the ability of an individual to establish direction for a working group of individuals who gain commitment from this group of members to this direction and who then motivate these members to achieve the direction’s outcomes. Leadership, however, requires neither gender qualifications nor someone with communal or agentic characteristics but one with instinct potential to fulfil responsibilities. The purpose of the current study was to investigate how women leaders perceive the underrepresentation of women in top sport leadership positions in Malaysia. Guided by an interpretative phenomenological analysis approach, data were collected through in-depth, face to face semi structured interviews, observations and document analysis involving seven women leaders in national sport organizations. The findings showed that women were underrepresented in top leadership positions and the subjects revealed perceived barriers which they believe impede women’s ascend in top leadership positions. These barriers include personal limitations which include self-limiting behaviors and work-life conflict among women; sociocultural factors consisting of traditional practices and society’s perceptions; and organizational factors consisting of all-men’s network, gender discrimination and conflict among women. It was concluded that the underrepresentation of women sport leaders is a vicious cycle where there is a chain of events in which the response to one difficulty creates a new problem that intensify and aggravate the original situation.